Exhibition of Dielectric Property Based on Soil Class and Moisture Presence for Bengaluru District. (12th June 2022) - Kumar, Sujit; Ahalya, N.; Singh, Vikash; Patil, Pravin P.; Raghavendra Rao, A. V.; Nirmala Jyothsna, A.; Abhilash, P.; kushwah, Rupesh; Palukaran Thimothy, Sojan
Abstract : This research examined the dielectric characteristics of soils by utilizing four types of soil (clay-loam, loam, clay, and Frank) in a vector network analyzer (VNA) in the 600–8000 MHz microwave frequency range at ambient temperature (25°C ± 3°C). In this experiment, three observations were performed on the basis of soil moisture contents (dry, 33%, 66%, and 100% field capacities (CC)). Both actual (dielectric constant) and fictional (loss factor) parts of the dielectric characteristics improved with increasing soil moisture; however, the responses were not linear. It was observed that dry soil dielectric characteristics were deficient when compared to wet soil. In conclusion, the dielectric behavior of soil mainly was resolute by the moisture in the soil. Frank soil had considerably lower dielectric characteristics, while the Jain University (JU) clay soil had a far more significant dielectric loss factor.